The Influence of Work Motivation, Compensation, and Work Climate on Employee Performance at PT Steelindo Wahana Perkasa Bangka Belitung - Jodhie Anugrah; Kusuma Chandra Kirana; Epsilandri Septyarini (P3KM Politeknik Pertanian Negeri Samarinda, 2025)
This study examines the extent to which work motivation, compensation, and work climate influence employee performance at PT Steelindo Wahana Perkasa Bangka Belitung, a palm oil company located in East Belitung Regency. The research aims to analyze both the partial and simultaneous effects of these variables to provide deeper insights into the determinants of employee performance within plantation-based organizations. A quantitative research design was employed by distributing structured questionnaires to all sixty employees using a five-point Likert scale. Data quality was ensured through validity and reliability testing, followed by classical assumption tests to confirm the suitability of the dataset for regression analysis. Multiple linear regression was used to evaluate the relationships between independent variables and employee performance. The findings indicate that work motivation has a positive and significant effect on employee performance, demonstrating the importance of psychological and intrinsic drivers in enhancing productivity. In contrast, compensation and work climate do not show significant individual effects, suggesting that financial rewards and environmental conditions alone are insufficient to boost measurable performance outcomes. When analyzed simultaneously, the three variables collectively produce a significant effect, as reflected in a coefficient of determination of 0.134. This outcome highlights that employee performance emerges from the interaction of multiple internal factors rather than a single dominant determinant. The study offers practical implications for developing more effective human resource strategies and encourages future research to incorporate broader organizational variables for a more comprehensive model of performance.